In silico Screening Unveil the Great Potential of Ruminal Bacteria Synthesizing Lasso Peptides - Sabino, Yasmin Neves Vieira; Araújo, Katialaine Corrêa de; Assis, Fábia Giovana do Val de; Moreira, Sofia Magalhães; Lopes, Thaynara da Silva; Mendes, Tiago Antônio de Oliveira; Huws, Sharon Ann; Mantovani, Hilário C. (Frontiers in Microbiology, 2020)
Studies of rumen microbial ecology suggest that the capacity to produce antimicrobial peptides could be a useful trait in species competing for ecological niches in the ruminal ecosystem. However, little is known about the synthesis of lasso peptides by ruminal microorganisms. Here we analysed the distribution and diversity of lasso peptide gene clusters in 425 bacterial genomes from the rumen ecosystem. Genome mining was performed using antiSMASH 5, BAGEL4, and a database of well-known precursor sequences. The genomic context of the biosynthetic clusters was investigated to identify putative lasA genes and protein sequences from enzymes of the biosynthetic machinery were evaluated to identify conserved motifs. Metatranscriptome analysis evaluated the expression of the biosynthetic genes in the rumen microbiome. Several incomplete (n=23) and complete (n=11) putative lasso peptide clusters were detected in the genomes of ruminal bacteria. The complete gene clusters were exclusively found within the phylum Firmicutes, mainly (48%) in strains of the genus Butyrivibrio. The analysis of the genetic organization of complete putative lasso peptide clusters revealed the presence of co-occurring genes, including kinases (85%), transcriptional regulators (49%), and glycosyltransferases (36%). Moreover, a conserved pattern of cluster organization was detected between strains of the same genus/species. The maturation enzymes LasB, LasC, and LasD showed regions highly conserved, including the presence of a transglutaminase core in LasB, an asparagine synthetase domain in LasC, and an ABC-type transporter system in LasD. Phylogenetic trees of the essential biosynthetic proteins revealed that sequences split into monophyletic groups according to their shared single common ancestor. Metatranscriptome analyses indicated the expression of the lasso peptides biosynthetic genes within the active rumen microbiota. Overall, our in silico screening allowed the discovery of novel biosynthetic gene clusters in the genomes of ruminal bacteria and revealed several strains with the genetic potential to synthesize lasso peptides, suggesting that the ruminal microbiota represents a potential source of these promising peptides.